Kegiatan Penyuluhan Kesehatan Terhadap Tingkat Pengetahuan Tentang Penyakit HIV/AIDS di SMA Assanadiyah Kota Palembang - Herdiani, Rini; Solekah, Umi; M, Mariyam; S, Sunirah (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
HIV/AIDS is a health problem in the world, including in Indonesia. he number of HIV/AIDS cases continues to increase from year to year. Adolescents are included in a group that is vulnerable to exposure to HIV/AIDS. As an effort to prevent and transmit HIV/AIDS can be done through health promotion. This activity aims to provide health promotion through outreach activities about HIV/AIDS to students at SMA Assanadiyah Palembang. The method used is using pretest and posttest. The results of community service activities showed an increase in knowledge about HIV/AIDS as seen from the increase in the score obtained. The conclusion of this activity is that counseling activities are easily accepted and increase knowledge about HIV/AIDS for students of SMA Assanadiyah Palembang.